Fetal Akinesia/Hypokinesia and Arthrogryposis of Neuromuscular Origin: Etiologic Groups, Genetics, and Phenotypic Spectrum - Florencia Pérez‐Vidarte; Berta Estévez‐Arias; Leslie Matalonga; Delia Yubero; Anna Codina; Carlos Ortez; Julita Medina; Lidia DeSena DeCabo; Laura Carrera‐García; Jesica Expósito‐Escudero; Cristina Jou; Eduardo F. Tizzano; et al. (Annals of Clinical and Translational Neurology)
ABSTRACT Objective To provide a comprehensive clinical and genetic characterization of individuals with arthrogryposis multiplex congenita (AMC), focusing on the distribution of genetic etiologies across the neuromuscular spectrum and comparing myogenic and neurogenic subtypes. Methods A total of 105 individuals with AMC were clinically and genetically evaluated in a single‐center study. Participants were stratified based on the primary site of involvement, and further classification was performed for neuromuscular cases into neurogenic and myogenic subtypes. Genetic diagnoses were made through using a range of next‐generation sequencing techniques, including exome sequencing (42 individuals), gene panel testing (40 individuals), genome sequencing (24 individuals), and targeted‐gene testing in selected cases. In most individuals who underwent genome sequencing, this was preceded by exome or gene panel testing. Results Of the 105 individuals, 4 were classified as Amyoplasia and 1 as FARAD. Among the remaining 100 cases, 81 (81%) presented with neuromuscular AMC, with defects involving motor neurons/peripheral nerves (52%, 42/81), neuromuscular junctions (7%, 6/81), and skeletal muscle (41%, 33/81). A genetic diagnosis was achieved in 55% (55/100) of the entire cohort and in 58% (47/81) of individuals with neuromuscular AMC. The most frequently implicated genes were TTN (16%, 9/55), CHRNG (10.9%, 6/55), PIEZO2 (9.1%, 5/55), ZC4H2 (9.1%, 5/55), DYNC1H1 (7.2%, 4/55), MYH3 (5.4%, 3/55), and RYR1 (5.4%, 3/55). Diagnostic yield varied significantly between subgroups, with 84.6% (33/39) of myogenic AMC cases genetically resolved, compared to 33.3% (14/42) of neurogenic cases. TTN was the most common gene in myogenic AMC, while ZC4H2 and DYNC1H1 were predominant in neurogenic AMC. Interpretation This study provides a detailed phenotypic and genetic characterization of neuromuscular AMC, highlighting the most frequently affected genes and their associated phenotypes. The findings underscore the challenges in diagnosing a significant proportion of cases, especially within the neurogenic subgroup, and emphasize the importance of integrating detailed phenotypic data with genetic analysis to enhance diagnosis, prognosis, and management of family expectations.